Association between maternal diabetes mellitus and allergic diseases in children — A systematic review and meta‐analysis. Issue 5 (25th May 2021) - Li, Zhi; Yu, Mei; Wang, Pin; Qian, Hong; Fan, Yun; Li, Xiuzhu; Xu, Qiaoqiao; Wang, Xinru; Wang, Xu; Lu, Chuncheng
Abstract: Background: Existing knowledge suggests that gestational diabetes mellitus was inconsistently associated with offspring allergic diseases. The aim of this study was to identify the association between maternal diabetes mellitus and the risk of offspring allergic diseases by systematic review. Methods: We searched and retrieved three databases (PubMed, Web of Science, and Cochrane Library) for articles on the association between maternal diabetes mellitus and offspring allergic diseases published before December 31, 2019. Stata software version 16.0 was used for statistical analysis. Results: Eight published studies were included in this meta‐analysis. The pooled effect estimates showed the association between maternal diabetes mellitus and allergic outcomes, including asthma (OR: 1.13, 95% CI: 1.01‐1.27), wheezing (OR: 1.13, 95% CI: 1.07‐1.21), and atopic dermatitis (OR: 1.43, 95% CI: 1.22‐1.57). Maternal diabetes mellitus was not associated with the risk of allergic sensitization, with a pooled effect estimate of 1.07 (95% CI: 0.45, 2.58). Conclusion: Maternal diabetes mellitus may increase the risk of allergic diseases in their children. However, this finding should be validated with future large‐sample epidemiological studies covering a wider spectrum of allergic diseases.